E-cigarette Use Among Young Adults in the U.S. - Olfson, Mark (Am J Prev Med, 2019)
INTRODUCTION: Use of e-cigarettes is increasing among young adults in the U.S. Whether e-cigarette use serves as an aid to smoking reduction or cessation among young adults remains a matter of contention. This analysis examines patterns of e-cigarette use in relation to cigarette smoking in a nationally representative sample of U.S. young adults. METHODS: Data were analyzed from nationally representative U.S. adults, aged 18 to 35 years (n=12,415), in the 2012–2013 National Epidemiologic Survey on Alcohol and Related Conditions-III. Logistic regression assessed associations between e-cigarette use and smoking intensity, continuity, and reduction while controlling for several potential confounding factors. Data were analyzed in 2018. RESULTS: Among cigarette smokers, e-cigarette use was associated with higher odds of tobacco use disorder (AOR=2.58, 95% CI=1.73, 3.83) and daily cigarette smoking (AOR=1.67, 95% CI=1.73, 3.83). Among adults aged 26–35 years, e-cigarette use was also associated with heavy cigarette smoking (AOR=2.01, 95% CI=1.09, 3.74). Among lifetime smokers, e-cigarette use was associated with lower odds of stopping smoking (AOR=0.14, 95% CI=0.08, 0.23) and lower odds of a 50% reduction in cigarettes smoked per day (AOR=0.63, 95% CI=0.43, 0.93). Only 13.1% of young adults who ever used e-cigarettes reported using them to help stop or quit smoking. CONCLUSIONS: Use of e-cigarettes by U.S. young adults, most of which is not to help reduce smoking, is related to more rather than less frequent and intensive cigarette smoking.